Invested in Unsustainability? On the Psychosocial Patterning of Engagement in Practices. (1st June 2016) - Groves, Christopher; Henwood, Karen; Shirani, Fiona; Butler, Catherine; Parkhill, Karen; Pidgeon, Nick
Abstract : Understanding how and why practices may be transformed is vital for any transition towards socio-environmental sustainability. However, theorising and explaining the role of individual agency in practice change continues to present challenges. In this paper we propose that theories of practice can be usefully combined with a psychosocial framework to explain how agency is biographically patterned and how this patterning is a product of attachment relationships and emergent strategies for dealing with uncertainty. Biographical interview data from the project Energy Biographies is used to illustrate the ways in which this theoretical approach can enhance understanding of how potential for practice change may be opened up or obstructed.